Improving Human Resources Motivation In Tourism Entrepreneurship : A Review - Joko Setiyo; Heri Pratikto; Sopiah (International Journal of Science, Technology & Management, 2022)
The review of this article will discuss how to increase the motivation of human resources in entrepreneurship in the tourism sector. Rural areas can benefit from the entrepreneurial dynamics created by small tourism businesses, especially when linked to the lifestyle of each entrepreneur. Several researchers regarding the contribution of small tourism businesses to improve the rural economy. The potential role of rural communities to increase tourism in rural areas should not be ignored. Related to increasing the motivation of human resources in entrepreneurship in the field of tourism. This study explores the motivations and management practices of tourism entrepreneurship as well as the consequences of community actions, considering the data obtained from several small tourism entrepreneurs, the efficiency and success of entrepreneurship.